PENGARUH NET PROFIT MARGIN (NPM) PADA BANK RAKYAT INDONESIA (BRI) CABANG PALANGKA RAYA - Sunarmie Sunarmie; Pamungkur Pamungkur (Dinamika Ekonomi: Jurnal Ekonomi dan Bisnis, 2025)
This study aimed to identify the effect of operational efficiency ratio and cost efficiency ratio on net profit margin of Bank Rakyat Indonesia (BRI) parcial and simultaneously during the period of 2017-2024. This is a descriptive qualitative study. It was done in such a way by collecting data which is supporting factors of the effect between relevant variables to be analyzed later. The results suggested that (a) operational efficiency ratio (BOPO ratio) partially brings an adverse effect, while cost efficiency ratio (CER) in fact brings a positive effect. In case of Bank BRI, this is a result of the development of total non-interest expense, as an indicator of CER, in fact it can boost total sales which is an indicator of NPM, particularly in 2019, where the total sales increased when the bank suffered a loss, and (b) variable X1, operational efficiency ratio (BOPO ratio) partially affecting binding variables, brings an effect on net profit margin (NPM).